EFT (Emotional Freedom Technique) Method Intervention in Reducing the Risk of Work Stress in Female Health Workers - Betania Narwastu Tania; Mardjan Mardjan; Elly Trisnawati (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Background: Work stress is still one of the problems in the workplace. Survey results show that 55.2% of health workers in hospitals experience work stress. Health workers, especially female nurses and midwives, are more susceptible to stress and anxiety because of their dual roles as housewives and workers along with the work pressures that must be carried out. This study aims to determine the effectiveness of EFT in reducing work stress in female health workers (nakes) in hospitals. Method: The research design used was Quasi Experimental. The sample was health workers, namely nurses and inpatient midwives who worked with a shift work mechanism of 25 people and were measured twice. Intervention method in this study was EFT treatment which was carried out for 7 consecutive days with 3 repetitions in each treatment. ENSS questionnaire was used to assess work stress. Data that had been collected was processed and analyzed using the Paired Sample T-Test. Result: The research findings show that the difference in work stress reduction is 31.76. Analysis test shows p-value = 0.000 (?0.05) which means there is a significant difference between work stress before and after the intervention. This study proves that EFT treatment is effective in reducing the risk of work stress in health workers, especially nurses and midwives who work with irregular shift work mechanisms. The main implication of the results of this study is the innovation of work stress interventions in a way that is fun and easy for workers to do. Conclusion: EFT can be used as one of the efforts to reduce the risk of work stress in health workers in hospitals. This treatment can be adopted as a routine work program in controlling work stress in hospitals, so that it can be applied sustainably both at work and at home independently.